A racial equity approach to nonprofit hospitals’ community benefit programs: an exploratory study - Conley, Cherie; Lewis, Crytstal N.; Singh, Simone Rauscher (Frontiers in Public Health, 2025)
IntroductionThe aim of this study was to explore the factors and processes that drive nonprofit hospitals’ willingness and ability to implement equity-focused community benefit initiatives – specifically initiatives aimed at addressing social and structural determinants of health and inequities associated with racism.MethodsWe conducted a cross-sectional qualitative study using semi structured interviews guided by the EquIR Implementation science framework and Browne’s racial equity approach to community benefit program implementation. Browne’s racial equity approach includes five strategies: (1) prioritizing community building strategies in communities impacted most by racism, (2) allocating resources to address structural determinants that reflect racism, (3) providing leadership and employment opportunities for community members and organizations impacted by racism, (4) addressing and considering multiple intersecting identities, and (5) removing organizational barriers to allocating resources to address health inequities along racial lines.ResultsWe conducted 24 interviews with leaders of 23 hospitals and health systems representing the Northeast, South, Midwest and West United States regions. We used directed content analysis to analyze interview data. The racial equity strategies most often used were 1, 2, and 3. The strategies least likely to be mentioned were 4 and 5.Two of the 23 health systems engaged in all five strategies.ConclusionHealth systems have the potential, partnerships, and resources to incorporate a racial equity lens into the planning, design, and implementation of their community-based initiatives. Utilizing a racial equity approach that includes prioritizing affected communities and providing resources and strategies to overcome barriers to accessing those resources is a template that can be used by hospitals to get closer to more effectively achieving this goal.